Ethical and legal analysis of scientific research on corpses in Brazil - Bezerra, Patricia Melo; Borba, Marina de Neiva; Guerriero, Iara Coelho Zito; Dallari, Sueli Gandolfi (Revista Bioética, 2020)
Currently there is an increasing interest in publications on the use of corpses for research in Brazil and worldwide. Scientific evidence reveal that these studies have little ethical and regulatory control. In Brazil, the regulation of this subject is scarce and scattered among laws and sublegal normative acts, hindering the knowledge of ethical and legal practices adopted by researchers. This article analyzes the laws and norms for scientific research on corpses in Brazil through a corpus that underlies this type of research. From the 1940-2012 period, we found seven documents of the Brazilian legislation that gather information for ethical and clear research. Finally, we present guidelines and a protocol to be followed by researchers for the development of ethical and legal studies with corpses in Brazil.